Uncertainty models of vision sensors in mobile robot positioning - Skrzypczyński, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
This paper discusses how uncertainty models of vision-based positioning sensors can be used to support the planning and optimization of positioning actions for mobile robots. Two sensor types are considered: a global vision with overhead cameras, and an on-board camera observing artificial landmarks.
Keywords: mobile robots; vision sensors; positioning; uncertainty; action planning; multi-agent systems